UPAYA MENINGKATKAN HASIL BELAJAR DRAMA DAN AKTIVITAS SISWA MELALUI METODE ROLE PLAYING PADA SISWA KELAS V SD NEGERI 020 TEMBILAHAN HILIR - Ernani Ernani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
Indonesian language learning at SD Negeri 020 Tembilahan Hilir is currently not showing the expected results.The learning atmosphere is predominantly teachers and students' language skills are very low. Teachingactivities undertaken by teachers, less use or use of learning methods that vary. Such learning is less interestingand students become passive. The condition of Indonesian learning in class V SD Negeri 020 Tembilahan Hiliris still below the minimum mastery criteria. One of the methods used to increase learning activity is through roleplaying method. This research was conducted at SD Negeri 020 Tembilahan Hilir Kecamatan Tembilahan. Thisresearch was conducted in May 2016 with the subject of 25 students. The result of this research concludes thatlearning role playing method has a positive impact in improving students 'learning achievement which is markedby the improvement of students' learning mastery in every cycle, that is cycle I (56.00%) and cycle II (92.00%).Implementation of learning role playing method has a positive influence, which can increase aktivtas studentsare shown with the results of observation no more students who get less criteria.